Ct Patterns of Omental Pathology and to Determine the Validity of Omental Caking in Diagnosis of Ovarian Cancer - Muhammad Wasif Iqbal, Sumaira Aslam, Abdul Razaque, Naima Mujahid, Muhammad Javaid, Hammad Ahmed Butt, Aayat Ellahi, Simrah Sharjeel (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To depict and characterize CT patterns of omental pathology and to determine the validity of omental caking in diagnosis of ovarian cancer. Methodology: A cross-sectional study was conducted in a tertiary care center between January 2020 to February 2021. In this study, 64 consecutive female patients with omental pathology, scheduled for biopsy, surgery and follow up were included. All CT scans were reviewed and findings were discussed with the consultant radiologists. The results were compared and confirmed on histopathology by either open surgical biopsy or per-cutaneous needle biopsy. Result: A total of 64 patients were enrolled in the study. Omental caking on computed tomography was identified in 44 (68.8%) patients. Presence of Omental caking was significantly associated with ovarian cancer (p<0.001). The positive and negative predictive values were 86.4% and 75%, respectively. The sensitivity and specificity of omental caking as diagnostic criteria for ovarian cancer were 88.4% and 71.4%. Conclusion: CT scan is the modality of choice to detect omental pathology. In addition it depicts all other related or unrelated abnormalities as well as causative factors like ovarian carcinoma.